2010
DOI: 10.1021/la100031d
|View full text |Cite
|
Sign up to set email alerts
|

Drop Impact, Spreading, Splashing, and Penetration into Electrospun Nanofiber Mats

Abstract: Experiments were conducted to study peculiarities of drop impact onto electrospun polymer nanofiber mats. The nanofiber cross-sectional diameters were of the order of several hundred nanometers, the pore sizes in the mats of about several micrometers, and the mat thicknesses of the order of 200 microm. Polyacrylonitrile (PAN), a polymer which is partially wettable by water, was used to electrospin nanofiber mats. The experiments revealed that drop impact onto nanotextured surfaces of nanofiber mats produce spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(105 citation statements)
references
References 19 publications
2
103
0
Order By: Relevance
“…The higher the splashing parameter is, the greater the propensity for droplet breakup. The threshold between splashing and nonsplashing (K d ) has been reported to vary according the surface: For a smooth surface K d = 57.7 [25], for a bed of 5-μm fibers K d = 87 [27], and for a bed of 81-μm glass spheres K d = 120 [12]. The impacting droplet in this work has a splashing parameter K = 556, a value far exceeding these thresholds, indicating its propensity to splash.…”
Section: Particle Ejectionmentioning
confidence: 59%
“…The higher the splashing parameter is, the greater the propensity for droplet breakup. The threshold between splashing and nonsplashing (K d ) has been reported to vary according the surface: For a smooth surface K d = 57.7 [25], for a bed of 5-μm fibers K d = 87 [27], and for a bed of 81-μm glass spheres K d = 120 [12]. The impacting droplet in this work has a splashing parameter K = 556, a value far exceeding these thresholds, indicating its propensity to splash.…”
Section: Particle Ejectionmentioning
confidence: 59%
“…A novel approach in drop and spray cooling of microelectronic devices employs coating of hot surfaces with electrospun non-woven polymer nanofiber mats [8,9]. Electrospun nanofiber mats are nano-textured permeable materials comprising of individual polymer nanofibers (with diameter of about several hundred nanometers) which are randomly orientated in the mat plane.…”
Section: Introductionmentioning
confidence: 99%
“…Application of a nanofiber mat coating to a surface has been shown to promote droplet spreading and adhesion. 2 It also has been proposed and shown that if a metal surface is coated with polymer nanofiber mat, the mass loss can be minimized to a great amount 3 and ameliorate our capability to remove heat through spray cooling economically and effectively. The thermal and structural properties of four different polymer nanofiber mats were measured.…”
Section: Introductionmentioning
confidence: 99%